Trends in traffic collisions and injuries in Kyrgyzstan, 2003-2007 - Viola Artikova; Michael E Thompson; Elena Platonova; Gerald F Pyle; Samat Toimatov (The World Health Organization, 2011)
OBJECTIVE: To assess the epidemiological data on motor vehicle collisions, injuries and deaths in Kyrgyzstan to inform evidence-based policy development. METHODS: Data on motor vehicle collision and injury statistics covering 2003-2007 were obtained from official sources provided by the Department of Traffic Safety and the Ministry of Health's Republican Medical Information Centre.The data were analysed and compared with data derived from studies in other low- and middle-income countries. FINDINGS: Large heterogeneity between data sources was noted. Motor vehicle collisions caused by drivers increased twofold between 2003 and 2007. Reported motor vehicle collisions, deaths and injuries increased by 34%, 33% and 47%, respectively, over that period. Such increases were proportionately greater than the growth in population or in the number of registered motor vehicles.The proportion of injury attributable to motor vehicle collisions increased by 14% and the collision-related mortality rate increased by 39% in 2003-2007. CONCLUSION: In Kyrgyzstan, the number of motor vehicle collisions is rising and so is the number of those who are injured or killed in them. Reversing this trend will call for closer collaboration among relevant agencies and for a comprehensive surveillance system, along with operational improvements in emergency medical care, new and strictly enforced passenger safety laws and improvements to the transportation infrastructure.